Agriculture-nutrition linkages, cooking-time, intrahousehold equality among women and children: Evidence from Tajikistan - Takeshima, Hiroyuki; Akramov, Kamiljon T.; Park, Allen; Ilyasov, Jarilkasin; Ergasheva, Tanzila (International Food Policy Research Institute, 2019)
Household-level agriculture-nutrition linkage (ANL) tends to be strong in a rural subsistence setting with limited access to the food market. In such a context, markets for food processing services also may be imperfect, and consequently a household’s time-investments in cooking may become important. Using the primary data in Tajikistan, we show that longer periods of time dedicated to cooking by women in the household often significantly enhance household-level ANL. Furthermore, an increase in the diversity, scale, and efficiency of household production, as well as longer cooking time, can also reduce intrahousehold inequality in nutritional outcomes among women and children. These effects are stronger in areas with lower nighttime light intensity and for households with lower values of cooking assets. In a context where household-level ANL is strong, ANL may also depend on households’ self-production of complementary inputs, including cooking services. This dependence reveals both unique opportunities for and vulnerabilities of ANL for the rural poor.